Strategic analysis of body composition indices and resting platelet ATP levels in professional soccer players for better platelet-rich plasma therapy - Ushiki, Takashi; Mochizuki, Tomoharu; Suzuki, Katsuya; Kamimura, Masami; Ishiguro, Hajime; Suwabe, Tatsuya; Watanabe, Satoshi; Omori, Go; Yamamoto, Noriaki; Kawase, Tomoyuki (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Autologous platelet-rich plasma (PRP) therapy is ambiguously thought to be more effective in elite athletes than in sedentary patients, although the possible importance of recipient responsiveness remains poorly understood. To address this issue, along with the well-known PRP quality, in this initial study, we evaluated two candidate biomarkers: body composition indices (BCIs), which reflect systemic physical conditions, and resting platelet ATP levels, which reflect platelet energy expenditure and the mass of energy generation units. Methods: In this cross-sectional cohort study, blood samples were collected from male professional soccer players (PSPs) on a local professional team during the off-season and platelet ATP levels were quantified using an ATP luminescence assay kit. BCIs were measured using the body mass impedance method. Age-matched male sedentary participants were used as the controls. Result: Among the BCIs, the body mass index, basal metabolic rate (BMR), and skeletal muscle weight levels were higher in the PSPs than in the controls. The platelet ATP levels in the PSPs group were significantly lower than those in the control group. The correlation between BMR and platelet ATP levels was moderately negative in the control group, but weakly positive in the PSPs group. Conclusion: Owing to regular physical exercise, PSPs had higher BMR levels and lower platelet ATP levels without a significant mutual correlation compared to sedentary controls. This study did not indicate the influence of these biomarkers on the success of PRP therapy but provided evidence for a better understanding of PRP therapy, particularly for elite athletes.